Leading in the Age of Super-Transparency - Austin, Robert; Upton, David (MIT Sloan Management Review, 2016)
When Martha Payne, a 9-year-old student in Argyll, Scotland, started a blog in April 2012 to photograph and rate her school lunches, she had no idea of the stir she would cause. The blog logged 2 million hits in its first six weeks. When the local area council asked her to stop, an online firestorm ensued and the council reversed its decision. It's a familiar story - every day, images or events with the potential to incite passions get captured digitally, posted to the Web, and "go viral." With social media, people share their experiences with friends or followers, who share with more people. Seemingly insignificant occurrences can strike a nerve with a nascent virtual community, and unsuspecting parties must respond to a dicey new problem. The capacity to generate causes and controversies almost instantly may be the most salient aspect of what authors Robert D. Austin and David M. Upton call the "super-transparent society." Historically, the authors explain, people in a particular community were the only ones who paid attention to the local goings-on. When information moved outside of that environment, it was due to deliberate action: some identifiable person or organization moving it. If you wanted to guard information, you built a barrier. Many things have changed, particularly the volume of information. The article suggests several steps that can help managers meet the new expectations for transparency, including the following: Examine your assumptions about how you can keep information contained. Review your strategy for dealing with vulnerability to unintended transparency. Review operations for issues that might be problematic if revealed. Assume that others will put out information about your organization for their own reasons and that you won't be able to prevent it. Recognize that new information flows change what people consider to be fair.
Keywords: Career development; Plan de carrière